2020
DOI: 10.9734/ajmah/2020/v18i930239
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Birth Defects among Pediatric Surgical Patients: A 12-Year Analysis in a Tertiary-level Government Hospital in Bangladesh

Abstract: Aims: Birth defects are structural or functional abnormalities which occur during the intrauterine life but can be identified at birth or a later age. Birth defects are major public health concerns and the World Health organization (WHO) is supporting countries for earlier diagnosis and better treatment of these conditions. The aim of the study was to assess the hospital-based prevalence and types of birth defects among the surgical children from a part of the world where these are underreported. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Mortality from birth defects in a tertiary center in Bangladesh over 12 years ( n = 657). ARM anorectal malformation, HPD Hirschsprung disease, PUV posterior urethral valves, NIO neonatal intestinal obstruction, CDH congenital diaphragmatic hernia, TEF tracheoesophageal fistula [62]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mortality from birth defects in a tertiary center in Bangladesh over 12 years ( n = 657). ARM anorectal malformation, HPD Hirschsprung disease, PUV posterior urethral valves, NIO neonatal intestinal obstruction, CDH congenital diaphragmatic hernia, TEF tracheoesophageal fistula [62]…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive literature review on pediatric surgical outcomes in African LMIC demonstrated ARM mortality ranging from 0 to 25% and Hirschsprung’s disease mortality ranging from 0 to 23% [13]. Meanwhile, in a pediatric surgical ward in Bangladesh anorectal malformations were the most common cause of death [62] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation